2021
DOI: 10.33258/birci.v4i1.1757
|View full text |Cite
|
Sign up to set email alerts
|

Financial Factors and Non-Financial to Financial Distress Insurance Companies That Listed in Indonesia Stock Exchange

Abstract: This study aims to test the influence of financial factors in the form of liquidity, cash flow, company size, institutional ownership, earnings and the factors of non-financial form of the independent commissioner against the financial distress of insurance companies that listed in Indonesia stock Exchange. The population of this research as many as 17 of the insurance company. The sampling technique using purposive sampling method, so that the obtained 15 sample company for 4 years of observations of the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Meanwhile, the results of research by (Fahruzzulfa, Marota, & Iryani, 2021) show that the variables of the board of directors have no effect on financial distress. The results of (Liahmad, Utami, & Sitompul, 2021) research show that the variables of institutional ownership and managerial ownership negatively affect finncial distress.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, the results of research by (Fahruzzulfa, Marota, & Iryani, 2021) show that the variables of the board of directors have no effect on financial distress. The results of (Liahmad, Utami, & Sitompul, 2021) research show that the variables of institutional ownership and managerial ownership negatively affect finncial distress.…”
Section: Introductionmentioning
confidence: 93%
“…These oversight efforts make managers' personal problems controllable by institutional ownership as they become more effective. The high value of institutional ownership will make the level of financial difficulty lower because when the value increases, more optimal monitoring will be carried out by the institution so that it can improve the quality of the company with its increasing productivity, so that the company can avoid financial distress (Putra & Muslih, 2019) According to research by (Liahmad et al, 2021), institutional ownership has a negative impact on financial problems because larger institutional stock prices correlate with better z-score values, which reduces the likelihood of financial problems. Findings this is consistent with a study by (Ikhwana & Ritonga, 2021), which found that institutional ownership has a negative impact on financial distress because the company's financial problems will get worse the larger the institutional stock.…”
Section: Hypothesismentioning
confidence: 99%
“…Some of these businesses ultimately collapse (i.e., fail) (Amankwah-Amoah & . Businesses fail for an array of reasons, such as the size and type of a company or industry, entrepreneurs' characteristics, and financial distress (Liahmad et al, 2021;Mayr et al, 2021;Ucbasaran et al, 2013). Boyle and Desai (1991) introduced a four-quadrant matrix to conceptualize the apparent causes of business failure, including internal-administrative, internal-strategic, external-administrative, and external-strategic reasons.…”
Section: Overview Of Business Survival/failure Predictionmentioning
confidence: 99%
“…Besarnya aset ini akan menarik perhatian investor karena perusahaan yang memiliki aset yang besar memiliki sumberdaya lebih untuk menghadapi permasalahan keuangan dan menghindari financial distress. Penelitian terdahulu yang dilakukan oleh Liahmad et al, (2021), Syuhada & Muda, (2020), Pranita & Kristanti, (2018) menunjukkan ukuran perusahaan berpengaruh terhadap financial distress.…”
Section: Financial Distressunclassified